MODELING OF 1-DIMENSION CONTROLLED SOURCE AUDIO-FREQUENCY MAGNETOTELLURICS (CSAMT) DATA USING ZOHDY-OLDENBURG DIRECT INVERSION - IHSAN REZQA NIM: 12314070, MUHAMMAD
CSAMT is an electromagnetic method with an artificial source capable of generating data with a more stable signal than the magnetoteluric method. CSAMT data acquisition that is relatively fast and characteristics of the data that have good lateral resolution are not supported by an easy and simple modeling process.Therefore, a simple inversion method is needed so that it can model CSAMT data quickly and efficiently. Zohdy-Oldenburg direct inversion is a method that can overcome these problems for magnetotelluric data. Therefore this inversion method will be applied to model the 1-D CSAMT data. In this research, we will use synthetic data formed from variations of resistivity model and also CSAMT data from North Sulawesi geothermal field. Then we use two types of thickness model that is effective depth model and constantly increased thickness model. In the constantly increased thickness model, the first thickness and the corresponding increment are determined using grid search. The thickness model data are then combined with pseudo resistivity data to form the subsurface model. The resistivity value is then updated until the Error value reaches a minimum. Based on the inversion process,Zohdy-Oldenburg inversion method is able to produce calculation data that is fit with observation data. Subsurface models based on effective depth is able to produce better results than the constantly thickening model due to the effective depth better describes the subsurface conditions of CSAMT data. However, there is a discrepancy between the inversion result model and the actual model due to the presence of near-field data that does not represent the actual subsurface conditions.